Estimasi Kesalahan Pengukuran Berdasarkan CTT dan IRT Soal Tryout SBMPTN TPA Tahun 2018 di Kota Makassar - Indriani H Ismail (ChemEdu, 2021)
This research aims to estimate standard error of measurement with TCC and IRT approach and compare the most sensitive theory in estimating standard error of measurement about Tryout SBMPTN TPA Year 2018 in Makassar City. This research is descriptive - explorative research with quantitative approach. The subjects of this study were participants of SBMPTN tryout in 2018 in Makassar city as many as 455 examinee. Data source in this research is answer sheet of SBMPTN TPA trial tryout participants in Makassar City. The instrument used in this study, which is a matter of multiple choice of Academic Potential Test (TPA) consisting of 50 items. The result of standard error estimation based on CTT is SE.Meas = 2.95, SE.Est = 2.322 and SE.Pred = 3.743. While measurement error based on IRT is 0,349. IRT is more sensitive in estimating measurement error about Tryout SBMPTN TPA 2018 in Makassar city.